External capital access and new product launch in start-up firms with uncertain intellectual property rights - Diana Heger; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Classical patent literature assumes that patents grant well-defined legal rights to exclude others from practicing an invention. In this scenario, start-up companies benefit from the exclusive right to commercialize patent-protected inventions and the certification effect of patents which signals the ventures' 'quality' to investors. If the decision about patent applications is pending at the patent office patent rights become probabilistic and both effects may not realize. We show that start-up companies are reluctant to launch new products if patents are pending. Further, pending patents attract risk-seeking investors (venture capitalists), while more cautious investors (banks) do not react on pending patents.
urn:nbn:de:bsz:180-madoc-352497
Keywords: L26; O31; O34; 330; start-ups; patents; probabilistic patents; pending patents; access to finance; new product launch